Problem solving and computational thinking. Building synergies between conceptualization and coding starting from primary school - Roberto Trinchero (Firenze University Press, 2019)
Coding and computational thinking are two terms increasingly present in the scholastic debate of last years. The recent Italian guidelines and new scenarios (MIUR, 2018) have given to computational thinking an important role today in school. However, it is often confusing the teaching of coding (that is, the teaching of a specific programming language) with the teaching of computational thinking, that requires to take into account the relationships between this, problem solving and competences. In fact, coding is only one of the moments of computational thinking, which must be preceded by a moment of conceptualization, linked to the analysis and decomposition of the problems subject to codification. The article proposes reflections and useful hints for working on computational thinking starting from the first year of primary school, through a re-edition in the form of an educational game of the famous Logo language.   Problem solving e pensiero computazionale. Costruire sinergie tra concettualizzazione e codifica a partire dalla scuola primaria Coding e pensiero computazionale sono ormai due termini sempre più presenti nel dibattito scolastico già da alcuni anni e le recenti Indicazioni nazionali e nuovi scenari (MIUR, 2018) hanno dato ancor più risalto al ruolo che dovrebbero avere nella scuola odierna. Spesso però si confonde l'insegnare il coding, ossia uno specifico linguaggio di programmazione, con l'insegnare il pensiero computazionale, trascurando i rapporti che vi sono tra questo, il problem solving e l'esercizio di competenze. Il coding è infatti solo uno dei momenti del pensiero computazionale, che va preceduto da un momento di concettualizzazione, legato all'analisi e alla scomposizione dei problemi oggetto di codifica. L'articolo propone riflessioni e spunti operativi utili per lavorare sul pensiero computazionale a partire dal primo anno della scuola primaria, attraverso una riedizione in forma di gioco didattico del celebre linguaggio Logo.